Mongolia Diagnostic Review of Consumer Protection and Financial Literacy : Volume 1. Key Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
The Mongolian economy has grown very rapidly following the discovery of significant mineral deposits. Large investments in the mining sector have led to increased capital inflows, resulting in cheap external funding for banks and rapid credit expansion. Loans to households increased at the staggering pace of 80 percent from 2010 to 2011, despite Mongolia’s history of banking crises. Loans to Small and medium sized enterprises (SMEs) have increased by some 65 percent in the same year. Although over 78 percent of adult Mongolians have accounts at formal financial institutions and over 61 percent have debit cards - far exceeding the average in the East Asia and Pacific region - in many respects the legal and regulatory framework and enforcement have not kept pace with the expansion of lending. Some important segments of the financial sector, such as securities and insurance, are still lagging due to low consumer awareness and low levels of savings. A number of reforms have been introduced to expand the financial services market but it is clear that consumer protection and financial literacy need to be addressed in a more systematic way. This World Bank’s diagnostic review provides a detailed assessment of the institutional, legal, and regulatory framework in three segments of the financial sector: banking, securities, and insurance. Volume I summarizes the key findings and recommendations of the review and volume II presents a detailed assessment of each financial segment compared to the good practices for financial consumer protection.